Seeing Gender: Perceptual Representations of Transgender Individuals. Issue 4 (May 2020) - Howansky, Kristina; Albuja, Analia; Cole, Shana
In four studies, we explored perceptual representations of the gender-typicality of transgender individuals. In Studies 1a and 1b, participants ( N = 237) created an avatar based on an image of an individual who disclosed being transgender or did not. Avatars generated in the transgender condition were less gender-typical—that is, transmen were less masculine and transwomen were less feminine—than those created in the control condition. In Study 2 ( N = 368), using a unique visual matching task, participants represented a target labeled transgender as less gender-typical than the same target labeled cisgender. In Study 3 ( N = 228), perceptual representations of transwomen as less gender-typical led to lower acceptability of feminine behavior and less endorsement that the target should be categorized as female. We discuss how biased perceptual representations may contribute to the stigmatization and marginalization of transgender individuals.